Cannot See the Wood for the Trees? <subtitle>Arnold von Harff’s Perception of the Natural World along the Mediterranean Roads (1496-1498)</subtitle> - Cécile Bruyet (Journal for the History of Environment and Society, 2022)
Abstract Wondering how medieval people perceived their environment has long moved scholars onto untamed research paths. A strong focus on scholastic writings as sources has left an unfinished picture of medieval societies’ perceptions of nature. Pilgrimage accounts written by lay authors offer a rare opportunity to explore other perspectives on nature, although of course in a setting which was profoundly shaped by religious experience and tradition. Through the example of Arnold von Harff, travelling between 1496 and 1498 in the Mediterranean, I propose methods to recognise the different coexisting attitudes towards the natural world, theorised by David Herlihy, in secular writings. Combining discourse analysis with literary GIS, I suggest some explanations as to why travellers would switch between attitudes along their journey, and how spatio-temporal parameters influenced their decisions. As a result, we understand that fear was only one of von Harff’s many attitudes to the natural world, and that his ability to stage different aspects of his identity was firmly determining his perception(s) of nature. By interpreting the landscapes in the Eastern and Western Mediterranean differently, von Harff could learn from and about the environment, suggesting that secular travel was commendable along the allegedly strict pilgrimage roads.